Compreendendo o portador HIV/Aids usuário de drogas - Souza, Nilzemar Ribeiro de; Vietta, Edna Paciência (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Airoing to cooperate to the comprehension of HN / Aids barer behavior face to his/her illness, we tried to identify the knowledge , attitudes, fee lings and beliefs these patients have about this illness, the conceptions that influence the persistence of the stigma and both, negative postures in the interacion with his/her relatives. To manage this present research we used as a theorical reference the "Health Belief Model" suggested by Rosentock, 1996. We made use of patients’ statements, to the comprehension of the subjects studied making use of a qualitative methodology. The research was made in the interior of the Scholl Arobulatory. Escola de Enfermagem de Passos - UEMG, where eleven patients, were interviewed, bering ali drug users and having a confirmed diagnosis of HIV/ Aids. The study allowed to understand that facing the diagnosis, the HN / Aids bearers get away from their friends and family, fearing to be refused by relatives, feeling sometimes to be questioned and frequently reminded that they are HN / Aids bearers, what makes them increase their biames. When they don’t have enough information, they are afraid of approaching to people they love fearing contaminate them. We concluded that nurses must be accustomed to possible conilicts that may happen in such situations feelings the influence of a family dynamic that appears as a consequence of emotional problems that arise.